Implementasi Penjadwalan Pertandingan Olahraga Otomatis Berbasis Website Dengan Metode Algoritma Genetika (Genetic Algorithm) (Studi Kasus : Karang Taruna Genta Sabanusa) - Dika Zaeni Mustofa (CV. Multi Kreasi Media, 2025)
Manual scheduling of sports events often encounters obstacles such as errors, long durations, and schedule conflicts. The youth organization Karang Taruna Genta Sabanusa faces similar issues in managing sports activities. An automated scheduling system based on Genetic Algorithms has been developed to solve this problem quickly, efficiently, and accurately. Genetic Algorithms mimic biological evolutionary processes to find optimal solutions in complex scheduling, reducing manual errors, and optimizing the use of sports facilities. This system also facilitates access for both admins and participants at any time. Thus, this solution is effective for managing tournaments and can be used by other organizations in need of a fast, flexible, and technology-based schedule.